The Power Proof Of Deed Under Hand Is Associated With The Authority Of Notary In Legalization And Waarmerking Based On Law Number 2 Of 2014 On Notary Position (Study On Several Notary Offices In Malang Regency) - Ba’agil, Hamzah; Suratman, Suratman; Sunardi, Sunardi (International Significance of Notary, 2022)
the deed under hand is a free-form deed. The making of which does not have to be in the presence of an authorized public official, still has the power of proof as long as it is not denied by the maker and if it must be proven, the proof must also be equipped with witnesses and other evidence. Deed under hand can be made by a notary. It can be in the form of legalization and waarmeking. So it can formulation of the problem as follows: 1. What is the notarial authority related to the deed under the legalized hand legalisasiand waarmerking ?, 2. How is the strength of the deed under hand that has legalisasi dan been legalized andwaarmerking in proving the case at trial ?, 3. What is the notary's responsibility for the deed under the hand that has legalisasi dan been legalized and waarmerking?. The research method used is empirical juridical approach. It can be concluded that the notarial Authority related to the deed under legalisasi the legalized and waarmerking, in accordance with the notary's definition based on Article 1 Item 1 joint article 15 Paragraph 1 and 2 of Law Number 2 of 2014 concerning the position of notary, that the Notary is authorized to certify the signature and book The Deed. The power of proof of the deed under the legalized hand and waarmerking in civil cases legalisasi , as long as the deed under the legalized hand is not denied or denied by the parties, the deed under the hand has perfect legal force. The notary's responsibility for the deed under the hand that has been legalized and waarmerking, the notary does not have public responsibility in the deed under the hand that is legalized or waarmerking, the notary is responsible for ensuring that the parties who sign and make the agreement.Keywords: Power Of Deed, Notary, Legalization, Waarmeking